Perceptions and Possibilities: Renewable Energy on the UW-Madison Campus - Burg, Ally; Eibergen, Andrea; Hersh, Jordan; Kazar, Suzie (My University, 2017)
This study examined the perceptions and possibilities of future renewable energy utilization on the University of Wisconsin-Madison campus to determine the realistic future of implementation. We accomplished this through GIS site suitability analysis, a survey of UW-Madison students, and interviews with UW-Madison professionals and experts on renewable energy. Renewable energy on campus is not ideal due to lack of space and varying complexities with campus infrastructure, administrative politics, and economic considerations. However, strong support for renewable energy from students demonstrates the interest for UW-Madison to source its energy responsibly. Information gathered from our interviews suggests that an off-campus investment is one of the best paths to clean energy. The University administration should further their own interest in renewable energy, as well as considering energy conservation and efficiency.
Includes Maps, Photographs, Figures, Diagrams, Appendices and Bibliography.
Keywords: Renewable energy; University of Wisconsin-Madison